Skeletal muscle stem cells confer maturing macrophages anti‐inflammatory properties through insulin‐like growth factor‐2 - Fang, Jiankai (Stem Cells Transl Med, 2020)
Cytokines produced by immune cells have been demonstrated to act on muscle stem cells (MuSCs) and direct their fate and behavior during muscle repair and regeneration. Nevertheless, it is unclear whether and how MuSCs can also in turn modulate the properties of immune cells. Here, we showed that in vitro expanded MuSCs exhibited a potent anti‐inflammatory effect when infused into mice suffering from inflammatory bowel disease (IBD). Supernatant conditioned by MuSCs similarly ameliorated IBD. This beneficial effect of MuSCs was not observed when macrophages were depleted. The MuSC supernatant was found to greatly attenuate the expression of inflammatory cytokines but increase the expression of programmed death‐ligand 1 in macrophages treated with lipopolysaccharide and interferon gamma. Further analysis revealed that MuSCs produce a large amount of insulin‐like growth factor‐2 (IGF‐2) that instructs maturing macrophages to undergo oxidative phosphorylation and thus acquire anti‐inflammatory properties. Interestingly, the IGF‐2 production by MuSCs is much higher than by mesenchymal stem cells. Knockdown or neutralization of IGF‐2 abrogated the anti‐inflammatory effects of MuSCs and their therapeutic efficacy on IBD. Our study demonstrated that MuSCs possess a strong anti‐inflammatory property and the bidirectional interactions between immune cells and MuSCs have important implications in muscle‐related physiological and pathological conditions.